Characterization of fillets and skins from two varieties of genetically improved farmed Nile tilapia (Oreochromis niloticus) - Vinicius José Campos; Eliane Gasparino; José Wellington Rodrigues Lima Júnior; Angélica de Souza Khatlab; Marisa Silva Bastos; Thais Pacheco Santana; Fernanda Losi Alves Almeida; Maria Luiza Rodrigues de Souza; Marcos Antonio Matiucci; Gislaine Gonçalves Oliveira; Carlos Antonio Lopes de Oliveira; Ricardo Pereira Ribeiro; et al. (PLoS ONE, 2025)
Genetically improved farmed tilapia (GIFT) is a strain of Nile tilapia (Oreochromis niloticus) developed for improved production and commercial parameters. Skin color, one of the characteristics distinguishing tilapia varieties, is an important phenotypic trait associated with qualitative and productive performance. This study aimed to assess fillet and skin characteristics in GIFT Nile tilapia with black and red skin phenotypes. For this, 24 GIFT Nile tilapia from the same spawning stock were divided into two groups based on skin color, namely a black variety (dark skin) and a red variety (reddish skin). There were no significant differences in biometric parameters between varieties. Fish of the red variety had higher 2 h post-slaughter pH and muscle antioxidant capacity and lower yellow-blue axis value (b*), luminosity (L*), thawing loss, cooking loss, and conjugated diene content (P < 0.05). The skin of black tilapia exhibited higher force in the progressive tear test tear, and higher strength, tensile strength, deformation, and elongation in the traction and stretching test than that of red tilapia. Black tilapia skin had higher collagen and hydroxyproline contents. The skin of the red variety exhibited higher expression levels of alpha 1, 2, and 3 type I collagen genes, lower expression levels of the vimentin gene, and higher antioxidant capacity. The results suggest that skin color phenotype may be linked to important metabolic pathways influencing fish fillet and skin traits. These findings can support future research aimed at identifying optimal varieties of Nile tilapia for specific purposes and optimizing the utilization of filleting waste.